Guarding a Well-Ordered Space on a Mediterranean Island - Holod, Renata; Kahlaoui, Tarek (The Archaeology of Medieval Islamic Frontiers, 2019)
For Ifriqiya, the Maghrib, and the eastern coast of al-Andalus, a ribāṭ can be defined as a coastal point of defense meant to host ghazīs, warriors for the faith or volunteers on the basis of religious commitment. From the eighth century onward, ribāṭs stretched along the seashore of Islamic Maghrib from Tripoli (Ṭarāblus) up to the east coast of al-Andalus. These were typically connected to another urban structure with an immediately supporting rural environment, or they could be isolated structures supplied from the sea. In one sense, they functioned in much the same way as stations along the ‘Abbasid-Byzantine land
Keywords: Archéologie -- Djerba; Hâra, mosquée al- (Sedouikech, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba)